2020
DOI: 10.1021/acsmacrolett.0c00551
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Entanglement and Cooperative Dynamics in Entangled Solutions of Ring and Linear Polymers

Abstract: Understanding how entanglements affect the behavior of polymeric complex fluids is an open challenge in many fields. To elucidate the nature and consequence of entanglements in dense polymer solutions, we propose a novel method: a "dynamical entanglement analysis" (DEA) to extract spatiotemporal entanglement structures from the pairwise displacement correlation of entangled chains. By applying this method to large-scale molecular dynamics simulations of linear and unknotted, nonconcatenated ring polymers, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…This observation indicates that the dynamics in ring polymers without chain ends becomes spatially homogeneous and the mechanism of the chain motion is essentially different from the reptation model for linear polymers A plausible key feature for topological constraints in ring polymers is an inter-ring threading event. [39][40][41][42][43][44][45][46][47] In particular, Michieletto et al have proposed the "random pinning" procedure, wherein some fractions of rings are frozen, to investigate the role of threadings on the dynamics. 44 They demonstrated that random pinning can enhance the glass-like heterogeneous dynamics in ring polymers.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…This observation indicates that the dynamics in ring polymers without chain ends becomes spatially homogeneous and the mechanism of the chain motion is essentially different from the reptation model for linear polymers A plausible key feature for topological constraints in ring polymers is an inter-ring threading event. [39][40][41][42][43][44][45][46][47] In particular, Michieletto et al have proposed the "random pinning" procedure, wherein some fractions of rings are frozen, to investigate the role of threadings on the dynamics. 44 They demonstrated that random pinning can enhance the glass-like heterogeneous dynamics in ring polymers.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…It is evident that the observed MSD is dominated by the correlation ∆r 1 (τ )•∆r 2 (τ ) , which increases almost linearly with time. Note that the origin of measured correlation is not the coherent motion of the chromosomes inside the nucleus [18,19]. Rather, the above observation, in particular the linear scaling of the correlation, indicates that the two tracked loci move together with the nucleus undergoing Brownian motion.…”
mentioning
confidence: 80%
“…If the nucleus itself is quiescent, the displacement correlation ∆r 1 (τ ) • ∆r 2 (τ ) between two loci will become negligibly small compared to oMSD [18,19]. In this case, the mean square change in d(t) is reduced to approximately twice the oMSD.…”
mentioning
confidence: 99%
“…Ring polymers are the simplest class of topologically non-trivial polymers that manifestly depart from the predictions of theoretical cornerstones such as the reptation and tube models [1]. Over the last 3 decades, there have been several theoretical and experimental attempts at understanding the statics and dynamics of rings [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and yet their behaviour in entangled solutions is still poorly understood. Individual ring polymers in the melt or entangled solutions assume compact non-Gaussian conformations, which are distinct from the ones assumed by linear polymers.…”
Section: Introductionmentioning
confidence: 99%

Persistence Homology Of Entangled Rings

Landuzzi,
Nakamura,
Michieletto
et al. 2020
Preprint
Self Cite